Dampak Implementasi Program Bantuan Pangan Non Tunai (BPNT) Terhadap Ekonomi Keluarga Miskin (Studi Kasus : Di Kelurahan Longat Kecamatan Panyabungan Barat Kabupaten Mandailing Natal) - Aliruddin Aliruddin; Azhari Akmal Tarigan; Mawaddah Irham (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Non-cash Food Assistance Program (BPNT) is one of the policies set by the government government efforts to help reduce the burden of expenditure of the poor, through the program is expected to provide tangible benefits to the community through food subsidies provided by the government to the poor and is also expected to improve the welfare of beneficiaries. This study aims to determine how the impact of Non-cash Food Assistance program (BPNT) on the economy of poor families in the village of Longat District Panyabungan Barat Mandailing Natal. This research approach is qualitative by using descriptive method. Data sources used are primary data and secondary data taken with data collection techniques in the form of observation, interviews and documentation. The formulation of the problem in this study is how the impact of Non-cash Food Assistance program (BPNT) on the economy of poor families in the village Longat District Panyabungan Barat Mandailing Natal?. The results of this study indicate that the existence of the Non-cash Food Assistance Program (BPNT) in longat village has a good impact on the economy of beneficiary families (KPM) known from the reduced burden of community spending in meeting family food needs. and with the BPNT program implemented in Longat village, it also has a good impact on e-warung owners, which is known from the increase in sales turnover due to the increasing number of consumers. However, in the implementation of the Non-cash Food Assistance program (BPNT) in Longat Village is not maximized because there are still some indicators that have not been met such as in terms of the accuracy of the target recipients and the accuracy of the timing of the distribution of aid.